2021
DOI: 10.3389/fped.2020.605879
|View full text |Cite
|
Sign up to set email alerts
|

Related Factors of Patent Ductus Arteriosus in Preterm Infants: A Systematic Review and Meta-Analysis

Abstract: Background: Patent ductus arteriosus (PDA) is a dramatically harmful disease in the neonatal period, in particular common in preterm infants, and our study was to determine related factors of PDA in preterm infants.Methods: A comprehensive literature review was conducted in PubMed, EMBASE, and Web of Science. The pooled odds ratio and standard mean difference were calculated to compare dichotomous and continuous variables, respectively. In addition, we also assessed the heterogeneity and publication bias and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
(73 reference statements)
0
17
0
3
Order By: Relevance
“…This allowed the comparison of the different outcomes but at the cost of including only 18 studies on PDA. A recent meta-analysis by Liu et al evaluated several risk factors for developing PDA in preterm infants [ 26 ]. They found that the risk of developing PDA was slightly higher for boys than for girls but only included 28 studies in the analysis on sex differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the comparison of the different outcomes but at the cost of including only 18 studies on PDA. A recent meta-analysis by Liu et al evaluated several risk factors for developing PDA in preterm infants [ 26 ]. They found that the risk of developing PDA was slightly higher for boys than for girls but only included 28 studies in the analysis on sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned above, PDA in term and preterm newborns are two conditions with a different etiopathogenic background and therefore may have a different sex ratio. The results of two recent meta-analyses suggest that there is no sex difference in the risk of developing PDA among preterm infants [ 19 , 26 ], but these meta-analyses were limited by the small number of studies included.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology of the present study is based on that used in our previous meta-analyses on the association of several risk factors and the incidence of PDA and/or the response to pharmacological treatment of PDA (26,27,(32)(33)(34). The study was performed and reported according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) and meta-analysis of observational studies in epidemiology (MOOSE) guidelines [15]. Review protocol was registered in the PROSPERO international register of systematic reviews (ID= CRD42018095509).…”
Section: Methodsmentioning
confidence: 99%
“…Besides ­systemic and pulmonary vascular resistance, the size and shape of the PDA, gestational and postnatal age, underlying medical risk factors, viscosity of the blood, chemical mediators and drugs used are decisive factors for the clinical deterioration that either acutely or chronically contributes to organ damage ( Figure 3 ). 27 - 29 …”
Section: Clinical Impacts Of Hspdamentioning
confidence: 99%
“…Besides systemic and pulmonary vascular resistance, the size and shape of the PDA, gestational and postnatal age, underlying medical risk factors, viscosity of the blood, chemical mediators and drugs used are decisive factors for the clinical deterioration that either acutely or chronically contributes to organ damage (Figure 3). [27][28][29] Stealing blood flow from systemic to pulmonary circulation especially during the diastolic phase of circulation leads to decreased flow to organs resulting in organ compromise with the failure of autoregulation affecting the brain, myocardial, renal, and gut perfusion. 27,28 Although a hsPDA may have an impact on common neonatal morbidities, such as bronchopulmonary dysplasia (BPD), acute renal failure, necrotizing enterocolitis (NEC), pulmonary and IVH, neurodevelopmental impairment, and eventually mortality, clear evidence for a causal relationship between hsPDA and these conditions is scarce.…”
Section: Clinical Impacts Of Hspdamentioning
confidence: 99%